At the boundaries of word-formation: Contrastive coreference in 30 European languages - Angster, Marco (Morepress Books, 2023)
The book deals with the morphological expression of contrastive coreference in a wide range of European languages and is scientifically relevant under various respects. Its first interest is empirical, as it presents a detailed and well documented description of contrastive coreference markers in the main European language families and individual languages. Second, it is relevant from the theoretical point of view, since it proposes an analysis of the constructions in question in a well-defined theoretical framework, Construction Morphology, which represents one of the most dynamic and fruitful approaches to derivational morphology currently available. The book also deals with issues at the boundaries between derivational (and inflectional) morphology, syntax, semantics and pragmatics, thus being a valuable tool for researchers interested in all these domains. Finally, in discussing the origin and development of the constructions in question, the book is of interest for people interested in diachrony and language evolution.